Edukasi Sertifikasi Self Declare Kepada Pelaku Usaha Mikro, Kecil Dan Menengah (UMKM) Di Kec. Genteng Kota Surabaya - Siti Mardiyah; Baterun Kunsah; Fitrotin Azizah (Empowerment: Jurnal Pengabdian Masyarakat, 2023)
Halal-H aram is the  substance of the law and the needs of Muslims.  Along with the development of products on the market, it is difficult to detect halal.  The needs of halal products can be met by Micro Small Enterprises Menengah (MSMEs) kec.  Genteng Surabaya, but do not have knowledge of halal certification and how to apply. Therefore, education about  the halal self-declare certificate is needed facilitated by the SEHATI 22 program. The purpose of this activity is  to increase the knowledge of MSMEactors. Roof tiles regarding halal certification self declare SEHATI 22. Educational activities are carried out by counseling methods through 3 stages, namely Coordination, Implementationn and Creation of a siHalal account.  The success of activities is measured by indicators: 1. Participation of MSME actors in socialization;  2. Distribution of MSMEs in tile district; 3.Ownership of Business Parent Number (NIB); 4. Types of MSME products; 5. Ownership of siHalal account. The results of the activity describe the level of knowledge of MSMEs kec.  Glightly by measuring the percentage of  achievement of activity indicators:1. MSME participation in socialization activities 80%, 2. The distribution of MSMEs in 5 villages is 52% tile, 23% capacity, 7% finisher, 11% ketabang and 7% Kaliasin barong;  3.85% NIB ownership; 4. Types of MSME products 85% food and beverages; 5. 33% siHalal account ownership.  Based on the results of the activity, it was concluded that there was an increase in the knowledge of MSMEs kec. Genteng about  halal self-declare  certification so that it has the potential to get halal certification through the SEHATI22 program, especially food and beverage products that already have NIB and siHalal accounts.